2021
DOI: 10.4102/sajid.v36i1.262
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge, attitudes and practices of doctors, pharmacists and nurses on antimicrobials, antimicrobial resistance and antimicrobial stewardship in South Africa

Abstract: Background: Sustained injudicious and indiscriminate use of antimicrobials has exerted selection pressure for developing antimicrobial resistance (AMR), requiring behaviour change from healthcare professionals (HCPs) based on their knowledge, attitudes and practices (KAP) on antimicrobials, AMR and antimicrobial stewardship (AMS). Methods:A cross-sectional online questionnaire-based survey was conducted nationally amongst doctors, pharmacists and nurses from November 2017 to January 2018. The questionnaire com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 11 publications
6
9
0
Order By: Relevance
“… 28 Similar findings were reported in South Africa, in which gaps in knowledge, attitudes and practices regarding AMR were identified among pharmacists and nurses. 36 The current findings and those reported from other studies suggest the need for increasing training and educational activities concerning AMR. Alongside this, AMS programmes should be strengthened in all areas of clinical practice.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“… 28 Similar findings were reported in South Africa, in which gaps in knowledge, attitudes and practices regarding AMR were identified among pharmacists and nurses. 36 The current findings and those reported from other studies suggest the need for increasing training and educational activities concerning AMR. Alongside this, AMS programmes should be strengthened in all areas of clinical practice.…”
Section: Discussionsupporting
confidence: 76%
“…The survey on antibiotic use and resistance conducted among health workers in South Africa also had similar findings; the study revealed that health workers thought antibiotic resistance was a global and national problem, with a lower proportion of nurses compared with pharmacists who were aware of this. 36 This could mean that nurses thought antibiotic resistance was an issue but not significant or serious enough to be considered a public health problem. One way to address this negative attitude would be to include this message in future WAAW campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are aware that there have been a number of studies undertaken in South Africa to monitor prescribing and resistance patterns in ambulatory care; however, these have shown variable findings alongside requests for additional data to guide future strategies [ 14 , 24 , 35 , 36 , 37 ]. In addition, there have been concerns among physicians in South Africa regarding their knowledge of antibiotics and AMR as well as confidence with prescribing antibiotics [ 38 ]. Between 2003 and 2005, two pilot projects undertaken in KwaZulu-Natal (KZN) Province and Brits (North West Province) assessed antibiotic use and resistance.…”
Section: Introductionmentioning
confidence: 99%